2000
DOI: 10.1063/1.125705
|View full text |Cite
|
Sign up to set email alerts
|

Ohmic nanocontacts to GaAs using undoped and p-doped layers of low-temperature-grown GaAs

Abstract: The development and characterization of high-performance nanocontacts to n-GaAs are reported. The nanocontacts can be made to both undoped and p-doped low-temperature-grown GaAs ͑LTG:GaAs͒ cap layers. The geometry of the nanocontact is well characterized and requires the deposition of a 4 nm single-crystalline Au cluster onto an ohmic contact structure which features a chemically stable LTG:GaAs surface layer prepared using an ex situ chemical self-assembly technique. A self-assembled monolayer of xylyl dithio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…2, values of ρ c of approximately 1 × 10 −7 cm 2 and the maximum current density of approximately 1 × 10 7 A cm −2 are obtained. Both of these values are comparable to the values achieved in high-quality large-area ohmic contacts to n-type GaAs [16]. In this case, the measurement system limits the minimum ρ c which can be resolved, so the contact resistance may be somewhat lower than this value.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…2, values of ρ c of approximately 1 × 10 −7 cm 2 and the maximum current density of approximately 1 × 10 7 A cm −2 are obtained. Both of these values are comparable to the values achieved in high-quality large-area ohmic contacts to n-type GaAs [16]. In this case, the measurement system limits the minimum ρ c which can be resolved, so the contact resistance may be somewhat lower than this value.…”
supporting
confidence: 67%
“…The current-voltage characteristics of the nanocontact structures have been measured using ultra-high-vacuum (UHV) STM current-voltage spectroscopy in the near-contact regime, i.e. a regime in which the resistance between the STM tip and the cluster is reduced by bringing the tip in close proximity to the cluster [15,16]. STM tips used in this study have typical end shapes with diameters less than 15 nm, as observed from TEM micrographs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…27 Using this maximum current value, we determined an upper bound for r c of ~1 ¥ 10 -7 W·cm 2 and a lower bound for J max of ~1 ¥ 10 7 A/cm 2 for the nanocontact with the p-doped LTG:GaAs cap layer. 27 The difference in the contact properties between the samples can be qualitatively explained by the better surface stability of p-doped LTG:GaAs and the presence of mid-gap states near the Fermi level in this material.…”
Section: Resultsmentioning
confidence: 99%
“…27 Using this maximum current value, we determined an upper bound for r c of ~1 ¥ 10 -7 W·cm 2 and a lower bound for J max of ~1 ¥ 10 7 A/cm 2 for the nanocontact with the p-doped LTG:GaAs cap layer. 27 The difference in the contact properties between the samples can be qualitatively explained by the better surface stability of p-doped LTG:GaAs and the presence of mid-gap states near the Fermi level in this material. 26,27 The I(V) shape difference between measurements over the cluster and over the XYL-coated surface can also be qualitatively explained by the work function difference between the Au nanocluster and the Pt/Ir tip and the resulting surface barrier height difference between the two cases.…”
Section: Resultsmentioning
confidence: 99%